2012
DOI: 10.1176/appi.neuropsych.11080189
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Anterior Capsulotomy for Intractable Depression

Abstract: A group of eight patients with severe depression lasting 6 years or longer were treated with anterior capsulotomy and followed prospectively. Stereotactic surgery was used to produce radiofrequency lesions in the anterior limbs of both internal capsules. For all patients, there are follow-up data for at least 24 months. At 24-to-36 months postoperatively, four patients were either not-depressed or mildly depressed; one was mildly-to-moderately depressed; one was moderately-to-severely depressed; and only one r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 25 publications
0
38
0
1
Order By: Relevance
“…Capsulotomy involves a lesion in the anterior limb of the internal capsule, hence severing fronto-striatal and limbic projections. A recent study of 8 patients with treatmentrefractory depression found that bilateral anterior capsulotomy resulted in complete or partial remission in 4 patients at the 2-3 year follow-up [84].…”
Section: Major Depression and Obsessive-compulsive Disordermentioning
confidence: 98%
“…Capsulotomy involves a lesion in the anterior limb of the internal capsule, hence severing fronto-striatal and limbic projections. A recent study of 8 patients with treatmentrefractory depression found that bilateral anterior capsulotomy resulted in complete or partial remission in 4 patients at the 2-3 year follow-up [84].…”
Section: Major Depression and Obsessive-compulsive Disordermentioning
confidence: 98%
“…Hurwitz et al [44] of the Vancouver Limbic Surgery Group (VLSG) reported 8 patients with MDD who underwent bilateral anterior capsulotomy using radiofrequency lesions. MR imaging conducted postoperatively found the ellipsoidal lesion volumes to be, on average, 4.8 × 4.4 × 14.2 mm, and 5.8 × 5.1 × 14.8 mm in diameter for the left and right hemispheres, respectively [44].…”
Section: Anterior Capsulotomymentioning
confidence: 99%
“…MR imaging conducted postoperatively found the ellipsoidal lesion volumes to be, on average, 4.8 × 4.4 × 14.2 mm, and 5.8 × 5.1 × 14.8 mm in diameter for the left and right hemispheres, respectively [44]. The procedure was well-tolerated by 7 of the 8 patients, with 1 patient developing akinetic mutism followed by dementia with parkinsonism, ultimately dying 2 years postoperatively due to renal failure [44]. Autopsy revealed extensive arteriolosclerosis secondary to a 40-year history of hypertension, which was deemed responsible for his vascular dementia [44].…”
Section: Anterior Capsulotomymentioning
confidence: 99%
See 2 more Smart Citations